Optimal International Agreement and Treatment of Domestic Subsidy - LEE, Gea M. (Institutional Knowledge at Singapore Management University, 2012)
We investigate how a domestic subsidy is treated in an international agreement, when a government, having incentive to use its domestic subsidy as a means of import protection, can disguise its protective use of subsidy as a legitimate intervention with which to address a market imperfection. We show that any optimal agreement, as opposed to the conventional message of the targeting principle, restricts the home government’s freedom to select its domestic subsidy in order to increase the market-access level for foreign exporters. Our finding suggests that a proper restriction on domestic subsidy is somewhere between GATT and WTO rules.